Análise sobre o uso de estratégias de localização em traduções de cartas pessoais - Viana, Rodrigo Emanuel Martins (2024)
This paper looks at the importance of localization in the process of translating personal letters exchanged between English-speaking sponsors and Portuguese-speaking Brazilian sponsored children, in the context of a non-profit evangelical Christian institution whose main objective is to assist children in vulnerable situations through partnerships with social programs already established in Christian churches located in communities around the world and through the sponsorship system in operation in the state of Ceará, Northeast Brazil. We emphasize how the practice of localization contributes to more effective and emotionally meaningful intercultural communication. We highlight that localization goes far beyond literal translation, in that the content of the letters is adapted to respect the cultural and linguistic nuances of the recipients, which is essential for building stronger personal relationships. The methodology used was bibliographical and documentary. Theoretical studies on translation, localization and intercultural communication were analyzed, as well as examples taken from real letters exchanged between sponsors and sponsored children, followed by the translation and localization solutions found by the professional responsible (this author) to ensure better communication between the parties. The results indicate that localization allows for a clearer and more meaningful transmission of the intentions and feelings expressed in the letters, overcoming cultural barriers that could compromise communication. It is concluded that localization is indispensable for ensuring that messages reach their goal in an authentic and meaningful way, promoting a more human and enriching relationship between sponsors and sponsored children.